Prevention Of Bullying in Adolescents with Assertive Communication and Happy Spiritual - Alviana, Fifi; Setyawati, Ari; Chadzik Masruri, Muhammad; Hofsoh, Mutingatul (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Mental health is not only needed in adulthood but adolescent stage development is indispensable. The adolescent stage of development is the golden stage in determining adulthood. Bullying is a behaviour that can inhibit adolescence by damaging physical and psychological development. The goal of PKM is to improve mental health by stopping bullying (assertive communication and spiritual happiness) in adolescents. The PKM method uses health education and demonstration. The participants in this activity were 30 students. The results of the activity evaluation found that 15% of adolescents understood enough and 85% of adolescents understood the concept of bullying and bullying prevention. Community service for adolescents is effective in increasing understanding and prevention of bullying.